The study on range of motion of hip and knee in prayer by adult Muslim males. A preliminary report - Sharifudin, Mohd Ariff; Arshad, Ahmad Afiq; MH, Johari; Rahimin Affandi, Muhammad Ali Sajjad; Sulong, Ahmad Fadzli; Taib, Mai Nurul Ashikin; Che Mohamad, Che Anuar; Roslan, Rosazra; Ab. Rahman, Norhafiza (International Islamic University Malaysia, 2015)
Introduction: Praying represents a fundamental activity of daily living in Muslim community. Muslims need to adopt several postures that require deep flexion of the knee and hip to perform this daily obligation. This is a preliminary report of the study on hip and knee range of motion conducted to obtain normative passive and functional range of flexion data during Muslim prayers in both weight-bearing joints of normal Muslim adults. Methods: A cohort of Malay men aged between 20 to 30 years was recruited in this cross-sectional study. Passive range of motion and flexion angles of the joints in various postures during prayer were measured using a standard goniometer. The difference against existing normative range of motion database available and the influence of various factors were analysed. Factors analysed include body mass index and other anthropometric measurements. Results: Sixty participants recruited for the preliminary phase of this study. The mean (SD) of passive hip and knee flexions were higher compared to other existing normative range of motion database. A unit increase in body mass index will have 0.782 units lower of knee range of motion. The hip and knee flexion arc were from 74.1° to 119.0° and from 3.3° to 119.7° respectively. Conclusion: The range of motion involved for prayers was more for the knee but less for the hip as compared to the measured passive range of motion. Body mass index has a significant linear negative relationship with the passive range of motion of the knee, but not the hip.